Confronting racism as a healthcare challenge: A teaching and learning approach - T. Dada; S. Lowe; P. Whybrow (Springer, 2024)
Abstract Across the United Kingdom, medical schools are acknowledging the need to respond to inequalities experienced by minority groups, racism within healthcare, and the need to decolonise medical curricula. Understanding the impact of structural racism is increasingly recognised as part of health professionals' training. In this paper we report the delivery of a new lecture and workshop on racism to first year medical students at Hull York Medical School, aimed to teach students about structural racism and the impact it has on health and healthcare services. Whereas comparable training programmes focus on personal values of inclusivity and diversity, these sessions encourage students to consider the reality of racism as part of health and healthcare experiences. The session includes conceptual content alongside applied examples of microaggression experienced by a healthcare professional. We report the results of student feedback attained through surveys using Likert scales and free text. We conclude by discussing the benefits of teaching medical students about racism, and its impact on patients and staff, rather than just inclusive practice.